Infestation, damage and natural enemies of Heteropsylla texana on algarrobo (Prosopis sp.) in Tongorrape (Motupe-Lambayeque) - Mormontoy, Shirley (2020)
Algarrobo trees, Prosopis sp., were assessed at Tongorrape forest (Motupe-Lambayeque) in order to know infestation and damages levels of Heteropsylla texana Crawford, and natural enemies of the pest. Assessments, 10 in total, were carried out each 15 days from march to july, 2014. Algarrobo trees were selected taking on account similarity in height, age and foliage density. Infestation was evaluated with a scale from grade 0 to 5 on five terminal buds per tree. On each tree, by sight, foliage damage intensity was determined under a scale from grade 0 to 5. Terminal buds were conditioned on plastic jars to carry them to an insect recovery laboratory. Insect identification was carried out at La Molina-Lima SENASA entomological museum. Infestation varied from grade 1 to 3, which means that psilid population level was from low to moderate, while damage intensity varied from 2 to 3 grade, which means important damage on trees foliage. Paraneda pallidula gutticolis and Leucochrysa sp., were registered as important predators.